Education as a Strategic National Priority: Participation of the Public Library - M. N. Kolesnikova; I. S. Samoilov (Библиосфера, 2023)
Due to the multiple increase in internal and external challenges to national culture and values, the implementation of educational functions, especially among teen-agers and young people, becomes the key one in maintaining the stability of the moral potential of society. A special place in this issue is occupied by libraries that are not directly related to the education of students as schools and higher educational institutions, but are fully suitable for this through the implementation of their educational function. Enlightenment is closely related to the task of education, since it is a part of users socialization. The aim of the article is to show the need to revive the direction of training librarians in higher educational institutions, who would have the competence to solve strategic tasks of the state cultural and educational policy for the protection, preservation and strengthening of traditional values and Russian identity, especially when working with children and youth.